PENGARUH KUALITAS PELAYANAN TERHADAP PARTISIPASI ANGGOTA PADA KOPERASI UNIT DESA (KUD) KUSUMA BAKTI DESA SIALANG KUBANG KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of service quality on member participation in the Kusuma Bakti Village Unit Cooperative (KUD) in Sialang Kubang Village, Perhentian Raja District, Kampar Regency. The subjects of this study were members of the Kusuma Bakti Village Unit Cooperative (KUD) totaling 778 members, the sample taken from the population was 89 members. With quantitative methods and data collection techniques using a questionnaire/questionnaire. The data analysis technique used is Simple Linear Regression Analysis. The data were collected through questionnaires, while the data analysis used was simple linear regression analysis through the SPSS version 26 program. The results showed that service quality had a positive effect on member participation in the Kusuma Bakti Village Unit Cooperative (KUD) Sialang Kubang Village, Perhentian Raja District, Kampar Regency. , it can be seen from the results of the determination test of R2 that R square is 0.628, which means that the percentage of the influence of service quality on member services is 62.8% while the other 37.2% is significantly affected by member participation.Key Words: Service quality, member participation